2024
DOI: 10.1094/pdis-05-23-0858-re
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Standardized Soybean Cyst Nematode Screening Assay in Pennycress and Identification of Resistant Germplasm

Abstract: The prospect of incorporating pennycress as an oilseed cover crop in the Midwest's corn-soybean rotation system has drawn researcher and farmer attention. The inclusion of pennycress will be beneficial as it provides an excellent soil cover to reduce soil erosion and nutrient leaching while serving as an additional source for oilseed production and income. However, pennycress is an alternative host for soybean cyst nematode (SCN), which is a major biological threat to soybean that needs to be addressed for sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Saini et al (1987) reported increased germination of pennycress seeds using GA and potassium nitrate. Recently, Basnet, Meinhardt, et al (2023) also showed that GA could promote seed germination in wild pennycress at room temperature. As mentioned earlier, mutants with low glucosinolate tend to exhibit low germination, potentially due to lowered napin levels, a protein type correlated with increased germination (Schatzki et al, 2014).…”
Section: Seed Dormancymentioning
confidence: 99%
See 3 more Smart Citations
“…Saini et al (1987) reported increased germination of pennycress seeds using GA and potassium nitrate. Recently, Basnet, Meinhardt, et al (2023) also showed that GA could promote seed germination in wild pennycress at room temperature. As mentioned earlier, mutants with low glucosinolate tend to exhibit low germination, potentially due to lowered napin levels, a protein type correlated with increased germination (Schatzki et al, 2014).…”
Section: Seed Dormancymentioning
confidence: 99%
“…Basnet, Meinhardt, et al. (2023), through a large germplasm screening assay, identified line Ames 32896 as consistently susceptible across two SCN Heterodera glycines type 7 and 1.2.5.7, which will be crucial to calculate FI in pennycress SCN experiments. This study further developed a pennycress SCN screening method and identified several moderately resistant pennycress lines.…”
Section: Biotic Pestsmentioning
confidence: 99%
See 2 more Smart Citations